PRACTICAL ASPECTS OF FORMATION CORPORATE COMPETENCY MODEL - A. Chornyi (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The article analyzes problems of corporate competency modeling on large domestic enterprises. The relevance of the issue is caused by absence of methodological rigor and appropriate organizational support during formation corporate competency models of most Ukrainian companies. Based on the analysis of foreign and domestic scientists' works, consulting companies' reports and own empirical experience we suggested 10-step competency formation model. it's determined difference between competency modelling for development of management staff and formation competency model, primarily, as a tool of corporate culture. it's explained features and differences of using certain techniques of competency modeling and emphasized importance of analysis methods during formation corporate competence models. According to competency modeling steps we identified appropriate organizational arrangements to eliminate the effect of rejection competency model by enterprises' employees. The result of this study is to disclose appropriateness of using competency modeling techniques according to the context.